Movements in Organizational Communication Research - McDonald, Jamie; McDonald, Jamie; Mitra, Rahul (Taylor & Francis Routledge [Imprint], 2019)
Movements in Organizational Communication Research is an essential resource for anyone wishing to become familiar with the current state of organizational communication research and key trends in the field. Seasoned organizational communication scholars will find that the book provides unique insights by way of the intergenerational dialogue that is found in the book, as well as the contributors' stories about their scholarly trajectories. Those who are new to the field will find that the book enables them to familiarize themselves with the field and become a part of the organizational communication scholarly community in an inviting and accessible way. Key features of the book include: A review of current issues and future directions in 13 topical areas of organizational communication research. Intergenerational dialogue and collaboration between both established and emerging scholars in their specialty areas. Reflections by the authors on their scholarly trajectories and how they became a part of the field. Discussion questions at the end of each chapter that prompt reflections and debate. The book also features online resources for instructors: Sample course syllabus Suggested case studies from the book Cases in Organization and Managerial Communication to align with this book's chapters The book is recommended as the anchor text for introductory graduate-level courses and upper-level undergraduate courses in organizational communication. It is also an excellent supplementary text for advanced doctoral-level courses in organizational communication, and courses in related fields such as organization studies, organizational behavior, and management.
eng
Keywords: Communication in organizations; Communication dans les organisations; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Organizational Behavior; Communication in organizations; Communication studies; Interdisciplinary studies; LANGUAGE ARTS & DISCIPLINES -- Communication; Reference, Information and Interdisciplinary subjects; business communication; corporate communication; Dennis Mumby; Handbook of organizational communication; management communication; organizational culture; strategic communication